What is the True Impact of Improved Cassava Varieties in Nigeria? - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
Nigerian farmers grow over 60 cassava varieties linked to the International Institute of Tropical Agriculture (IITA) (http://www.iita.org/) research efforts. While yields and the area under cassava have increased over the past decade in Nigeria, there is a lack of rigorous impact evidence—this despite cassava being a major source of food and income. The extent to which an agricultural technology is adopted is a critical input to examine productivity and welfare impacts resulting from adoption.